2007
DOI: 10.1038/nature06188
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells within tumour stroma promote breast cancer metastasis

Abstract: Mesenchymal stem cells have been recently described to localize to breast carcinomas, where they integrate into the tumour-associated stroma. However, the involvement of mesenchymal stem cells (or their derivatives) in tumour pathophysiology has not been addressed. Here, we demonstrate that bone-marrow-derived human mesenchymal stem cells, when mixed with otherwise weakly metastatic human breast carcinoma cells, cause the cancer cells to increase their metastatic potency greatly when this cell mixture is intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

110
2,502
16
42

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,870 publications
(2,670 citation statements)
references
References 31 publications
110
2,502
16
42
Order By: Relevance
“…CCR9 was associated with intestinal melanoma metastasis [112], and CCR10 with spread to LN [113]. CCR5 is expressed by Hodgkin lymphoma [114], in prostate cancer [115] and by mammary tumors [116].…”
Section: Tumor Cell Invasion and Migration To Distant Organsmentioning
confidence: 99%
“…CCR9 was associated with intestinal melanoma metastasis [112], and CCR10 with spread to LN [113]. CCR5 is expressed by Hodgkin lymphoma [114], in prostate cancer [115] and by mammary tumors [116].…”
Section: Tumor Cell Invasion and Migration To Distant Organsmentioning
confidence: 99%
“…It has been well demonstrated that MSCs are recruited to the site of tumor,9, 11, 12, 13, 14 playing a pivotal role by interfering with other immune cells present in the surrounding tumor tissue. For this reason, it is highly relevant to determine how MSCs exert their immunoregulatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the tumor coopts the regenerative capacity of the host1, 4 resulting in tumor's own survival and proliferation. MSCs can migrate to the sites of inflammation and damage5 within the tumor microenvironment 6, 7, 8, 9, 10. Consistently, MSCs are often found within tumors11 and promote cancer progression and enhance metastasis 9, 12.…”
Section: Introductionmentioning
confidence: 90%
“…Les travaux les plus récents se sont focalisés sur les mécanismes qui contribuent aux effets négatifs ou positifs des CSM sur la croissance tumorale (Tableau I). Parmi les études les plus remarquables, on peut citer celle de l'équipe de H. Weinberg qui a montré que les CSM mises au contact de cellules de cancer du sein produisaient la chimiokine CCL5 (connue aussi sous le nom de RANTES, regulated upon activation, normal T-cell expressed, and secreted ), qui était capable d'augmenter de manière spectaculaire la capacité métastatique des cellules tumorales [12]. L'hypersécrétion de CCL5 par les CSM serait secondaire à la production par les cellules tumorales soit d'IGF-1 (insulin-like growth factor-1) [13], soit d'un peptide pro-inflammatoire de 37 acides aminés (LL-37) qui induirait non seulement la production de CCL5, mais aussi celle de l'IL-6 (interleukine-6), l'IL-10 et du VEGF (vascular endothelial growth factor ) et stimulerait l'angiogenèse et la croissance des tumeurs ovariennes [14].…”
Section: Tropisme Des Csm Pour Les Sites Tumorauxunclassified